Melka Kunture (High Awash , Ethiopia) from 2,000,000 to 5,000 years ago (Salduie, 2023)
Melka Kunture is a cluster of prehistoric sites located in the Ethiopian highlands, at 2000-2200 m above sea level, in the Upper Awash basin. The climate is rather cool (annual mean temperature 17°) and rainy. Palynological results prove that the original vegetation was of Afromontane type, i.e. distinct from the savanna one which develops at lower elevations. After 60 years of excavations at 20 sites and in 60 archaeological levels, the sequence includes the Oldowan, the Acheulean, the Middle Stone Age and the Late Stone Age. Hominin fossils were discovered in direct association with the lithic technocomplexes. Ichnological levels provide information on the life and behaviour of hominins and fauna which printed their tracks. Research on the hominin adaptation to the climate and environment of the highlands is relevant to understand how and when the earliest peopling of Europe happened.
Keywords: Olduvayense; Achelense; Middle Stone Age; Late Stone Age; Hominin footprints